Transverse Colon Volvulus presenting as Bowel Obstruction, Atelectasis, and Displacement of the Right Lobe of the Liver into the left upper Abdominal Quadrant: a case report - Kayiira, Mubaraka; Muwanguzi, Eria; Kasozi, Derrick; Ayebare, Rogers; Musinguzi, Edwin; Orimunsi, Innocent; Okeny, Paul; Mbide, Peter; Serumaga, Timothy Arthur; Tamale, Nicholas (The Lancet HIV, 2022)
Transverse colon volvulus is an uncommon cause of intestinal obstruction. It is a surgical emergency that can lead to bowel infarction, peritonitis, and death. We report a case of transverse colon volvulus in a 35-year-old Congolese immigrant man who had a rare presentation with features of intestinal obstruction associated with right lung collapse and left mediastinal shift. This case is unusual because it presented with respiratory features that mimicked a pneumothorax in addition to features of intestinal obstruction. The use of point-of-care lung ultrasound was helpful in ruling out a pneumothorax, and this could help avoid situations such as unintentional chest drain insertions by other professionals who may encounter a similar case. Because transverse colon volvulus is rare, a high level of suspicion and awareness is required to make an accurate diagnosis.
Keywords: Point of care ultrasonography; Transverse colon volvulus; Displacement of the right lobe of the liver; Bowel obstruction; Right lung collapse